1966
DOI: 10.1128/jb.92.5.1298-1303.1966
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Structure of Brucella suis Spheroplasts

Abstract: BAUGHN, ROBERT E. (University of Tennessee, Memphis), AND BoB A. FREEMAN. Antigenic structure of Brucella suis spheroplasts. J. Bacteriol.. 92:1298-1303. 1966.-Immunoelectrophoresis was used to differentiate between the antigenic mosaics of normal cells of Brucella suis and of spheroplasts prepared by treatment with penicillin, glycine, and a combination of these agents. Smooth cells possessed at least 13 antigens, 10 of which were precipitated with homologous antiserum. Three additional antigens were visualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

1970
1970
1984
1984

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…The first peak contained most of the DNA and pentose; it also had considerable protein and RNA and most of the dermal toxicity. Immunoelectrophoresis of this fraction showed that it contained the major antigen E and minor antigen f of Baughn and Freeman (2). Since antigens E and f appeared in the void volume, the molecular sizes could not be determined with this gel.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…The first peak contained most of the DNA and pentose; it also had considerable protein and RNA and most of the dermal toxicity. Immunoelectrophoresis of this fraction showed that it contained the major antigen E and minor antigen f of Baughn and Freeman (2). Since antigens E and f appeared in the void volume, the molecular sizes could not be determined with this gel.…”
Section: Resultsmentioning
confidence: 90%
“…For interpreting the antigenic analyses in this and previous studies, the precipitating antigens are identified by a code in which negatively charged antigens are given number designations; positively charged and nonmigrating antigens are assigned arabic numerals. Further, strongly precipitating antigens are designated "major," and their numbers or letters appear in either italics or upper case (2). Separation of antigens by gel filtration.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations